Ratio of Seaweed Porridge Eucheuma cottonii and Sargassum sp. as a Sunscreen Cream Formula - Novi Luthfiyana; Nurjanah Nurjanah; Mala Nurilmala; Effionora Anwar; Taufik Hidayat (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
AbstractThe use of sunscreen is highly recommended to protect the health of the skin from ultraviolet radiation.The aim of this study were to get the best ratio sunscreen preparation of porridge E. cottonii and Sargassumsp. through the total test microbes, antioxidants and SPF value, get a stable cream preparations physicallythrough sensory test, pH, consistency, Cycling test and centrifugal test. The main materials used were E.cottonii, Sargassum sp. and raw materials stocks cream. This study used a completely randomized design(CRD), which consisted of four treatments with two replications.The results showed that the best ratio ofsunscreen cream was cream with the addition of E. cottonii and Sargassum (1:1). The result obtained wasthe absence of microbs at creams and porridge E. cottonii and Sargassum sp. The antioxidant activity of E.cottonii porridge 127.23 ± 2.77μg/mL, Sargassum sp. 119.66 ± 0.25 μg/mL, and cream 83.4 ± 0.03 μg/mL.Cream SPF value was 7.03 ± 0.01. Consumer acceptance of the products through sensory test ranged fromnormal to like. Sunscreen creams had good physical stability and the cream has a shelf life preparation oneyear.